Study to estimate the NIHS score and volume of stroke in predicting 30-day mortality in acute ischemic stroke patients - Dhanush Balaji S.; Abinaya Srinivasa Rangan; S. Prasanna Karthik; Karpaka Vinayakam Gopalakrishnan; Selva Balaji; Manoj Kumar S. (Romanian Medical Journal)
Background. Stroke is defined as a sudden onset of a neurological deficit attributed to a focal vascular cause. It is one of the leading causes of mortality and morbidity all over the world. The present study aimed to estimate the NIHS score and volume of stroke in predicting 30-day mortality in acute ischemic stroke patients. Material and methods. The present study was a prospective cross-sectional study conducted in 100 patients above 18 years old, of either gender, with symptoms of stroke for less than 24 hours, diagnosis of acute ischemic stroke based on history, physical examination, CT scan and/or diffusion weighted MRI scan performed during the first 24 hours. Results. In the present study, the mean age was 57.4±13.36 years. The volume of stroke on 1st day was 40. 75 ± 38.51, and on 30th day it was reduced to 31.94±33.20 which was statistically significant. NIHSS (National Institutes of Health Stroke Scale) score on day 1 was 9.70±5.22, and on day 30 it was 7.77±5.25, with a statistically significant difference (p=0.000). At the end of the 30 days, 10% mortality was observed. NIHSS score and volume of stroke were significantly associated with the 30-day outcome. Conclusion. In conclusion, integrating NIHSS scoring and stroke volume assessment into routine clinical practice enhances predictive accuracy for 30-day mortality in acute ischemic stroke patients. These findings advocate for early intervention strategies aimed at reducing stroke volume and improving neurological outcomes. Further research is recommended to validate these findings across diverse populations and settings, potentially refining acute stroke management protocol.